Advances in medical therapy for pericardial diseases. (2nd September 2018) - Galluzzo, Alessandro; Imazio, Massimo
ABSTRACT: Introduction : Medical therapy of pericardial diseases is moving forward to the road of evidence-based medicine and has improved in the last years because of the first randomized clinical trials in the area as well as new therapeutic options for recurrent pericarditis. Areas covered : The present review will focus on more recent advances with a special emphasis on the treatment of pericarditis, the area with more significant improvements in the last years. Medline/Pubmed Library were systematically screened with two specific key searches: 'pericarditis AND therapy' and 'pericardial effusion AND therapy'. The search was restricted to articles published in the last 5 years, in order to select the latest novelties in medical treatment and was restricted to 'human' studies and papers in English. Expert commentary : The anti-inflammatory therapy of pericarditis has been now well defined with first-line agents represented by nonsteroidal anti-inflammatory drugs plus colchicine, low-dose corticosteroids with slow tapering as second-line agents and for specific indications (e.g. specific systemic inflammatory diseases, renal failure, pregnancy, patients with interfering therapies such as oral anticoagulants), and third-line options in case of multiple recurrences (e.g. azathioprine, intravenous immunoglobulins, and especially anakinra).